(untitled) (Homoeopathy for All, 2023)
Obesity is a recognized medical disorder characterized by the accumulation of excessive body fat, resulting in various health complications and a potential decrease in life expectancy for those affected.1 Obesity and overweight have grown to be serious public health issues in both developing and rich nations, and they pose enormous difficulties for maintaining the gains in world health. The prevalence of overweight and obesity has risen in developing nations such as India due to demographic, epidemiological, and nutritional changes. These changes have resulted in a decline in the burden of communicable diseases and fertility rates, but non communicable diseases (NCDs) have become more prevalent.2